Bioavailability of orange juice (poly)phenols: the impact of short-term cessation of training by male endurance athletes - Pereira-Caro, G.; Polyviou, T.; Ludwig, I. A.; Nastase, A.-M.; Moreno-Rojas, J. M.; Garcia, A. L.; Malkova, D.; Crozier, A. (The American Journal of Clinical Nutrition, 2017)
Background: Physical exercise has been reported to increase the bioavailability of citrus flavanones.Objective: We investigated the bioavailability of orange juice (OJ) (poly)phenols in endurance-trained males before and after cessation of training for 7 d.Design: Ten fit, endurance-trained males, with a mean ± SD maximal oxygen consumption of 58.2 ± 5.3 mL · kg(-1) · min(-1), followed a low (poly)phenol diet for 2 d before drinking 500 mL of OJ containing 398 µmol of (poly)phenols, of which 330 µmol was flavanones. After the volunteers stopped training for 7 d the feeding study was repeated. Urine samples were collected 12 h pre- and 24 h post-OJ consumption. Bioavailability was assessed by the quantitative analysis of urinary flavanone metabolites and (poly)phenol catabolites with the use of high-pressure liquid chromatography-high resolution mass spectrometry.Results: During training, 0-24-h urinary excretion of flavanone metabolites, mainly hesperetin-3'-O-glucuronide, hesperetin-3'-sulfate, naringenin-4'-O-glucuronide, naringenin-7-O-glucuronide, was equivalent to 4.2% of OJ flavanone intake. This increased significantly to 5.2% when OJ was consumed after the volunteers stopped training for 7 d. Overall, this trend, although not significant, was also observed with OJ-derived colonic catabolites, which, after supplementation in the trained state, were excreted in amounts equivalent to 51% of intake compared with 59% after cessation of training. However, urinary excretion of 3 colonic catabolites of bacterial origin, most notably, 3-(3'-hydroxy-4'-methoxyphenyl)hydracrylic acid, did increase significantly when OJ was consumed postcessation compared with precessation of training. Data were also obtained on interindividual variations in flavanone bioavailability.Conclusions: A 7-d cessation of endurance training enhanced, rather than reduced, the bioavailability of OJ flavanones. The biological significance of these differences and whether they extend to the bioavailability of other dietary (poly)phenols remain to be determined. Hesperetin-3'-O-glucuronide and the colonic microbiota-derived catabolite 3-(3'-hydroxy-4'-methoxyphenyl)hydracrylic acid are key biomarkers of the consumption of hesperetin-O-glycoside-containing OJ and other citrus products.